The Relationship Between Quality Management Practices and Productivity in Revenue and Cost Management : A Study of Local Authorities in Peninsular Malaysia (Malaysian Management Journal, 2001)
The globalization and liberalization of the world economic system have brought us to an era where global competition is highly intense. The introduction of new technology and systems has greatly affected the performance of organizations. Quality is widely recognized as one of the important disciplines and strategies for competitiveness. This study examines the relationship between quality management practices and the productivity in revenue and cost management in local authorities. Three hundred twenty managers from eighty organizations participated in this study. Disproportionate stratified random sampling was used as the sampling technique from the population frame and the data were gathered through self-administered structured questionnaires. The results of the regression analysis showed that only two constructs among the seven quality management practices were found to be significantly related to productivity in revenue and cost management. The construct for employee focus has a positive association with the productivity in revenue and cost management whereas process management has a significant inverse relationship with the productivity in revenue and cost management. Thus, local authorities need to address these two constructs in order to achieve a higher level of productivity in revenue and cost management.